2010
DOI: 10.1111/j.1365-2265.2009.03716.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth hormone (GH) replacement on muscle strength in patients with GH‐deficiency: a meta‐analysis

Abstract: Evidence from short-term controlled studies fails to support a benefit on muscle strength of GH replacement in GHD patients, which is likely to occur over a longer time-course, as seen in open-label studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As such, GH may exert direct systemic effects via receptor dimerization or indirect effects via the stimulation of systemic or local IGF-I expression [1]; although, we did not observe changes in circulating IGF-I following either exercise protocol. Importantly, it is no longer thought that GH stimulates accretion of skeletal muscle mass in adults [5], considering that GH does not induce myofibrillar protein synthesis [2] and that exogenous GH administration does not improve muscle performance in healthy young individuals, GH-deficient individuals [49], or older men [8]. In humans, the primary roles of GH are as a key regulator of fuel metabolism and as an initiator of protein synthesis with connective tissue [50].…”
Section: Discussionmentioning
confidence: 99%
“…As such, GH may exert direct systemic effects via receptor dimerization or indirect effects via the stimulation of systemic or local IGF-I expression [1]; although, we did not observe changes in circulating IGF-I following either exercise protocol. Importantly, it is no longer thought that GH stimulates accretion of skeletal muscle mass in adults [5], considering that GH does not induce myofibrillar protein synthesis [2] and that exogenous GH administration does not improve muscle performance in healthy young individuals, GH-deficient individuals [49], or older men [8]. In humans, the primary roles of GH are as a key regulator of fuel metabolism and as an initiator of protein synthesis with connective tissue [50].…”
Section: Discussionmentioning
confidence: 99%
“… 10 Other similarly designed studies have not shown any such effect on exercise performance. 51 , 54 56 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IGF-1 also exerts an anabolic action on muscle, increasing the protein synthesis and decreasing the protein breakdown ( 41 , 42 ). In fact, IGF-1 elicits skeletal muscle cell proliferation and myocytes differentiation ( 42 ).…”
Section: Discussionmentioning
confidence: 99%